2022
DOI: 10.20517/2394-5079.2021.131
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma surveillance: current practice and future directions

Abstract: Hepatocellular carcinoma (HCC) is among the leading causes of cancer incidence and mortality worldwide. Surveillance of individuals with cirrhosis or other conditions that confer a high risk of HCC development is essential for early detection and improved overall survival. Biannual ultrasonography with or without alpha-fetoprotein is widely recommended as the standard method for HCC surveillance, but it has limited sensitivity in early disease and may be inadequate in certain individuals. This review article w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…Attempts have been made by studies to expand the Milan criteria using UCSF to accommodate more patients for a liver transplant; however, it was challenged due to the small sample size. 10 Our patient did not meet any of the above criteria considering the liver mass size of 12 × 6.5 cm, thus chemotherapy with atezolizumab plus bevacizumab was recommended. The IMBrave 150 study by Cheng et al demonstrated statistically significant and clinical improvement in both overall and progression-free survival for atezolizumab + bevacizumab versus sorafenib in patients with unresectable HCC who have not received prior systemic therapy.…”
Section: Discussionmentioning
confidence: 86%
“…Attempts have been made by studies to expand the Milan criteria using UCSF to accommodate more patients for a liver transplant; however, it was challenged due to the small sample size. 10 Our patient did not meet any of the above criteria considering the liver mass size of 12 × 6.5 cm, thus chemotherapy with atezolizumab plus bevacizumab was recommended. The IMBrave 150 study by Cheng et al demonstrated statistically significant and clinical improvement in both overall and progression-free survival for atezolizumab + bevacizumab versus sorafenib in patients with unresectable HCC who have not received prior systemic therapy.…”
Section: Discussionmentioning
confidence: 86%
“…As a metalloreductase involved in cellular iron and copper homeostasis, STEAP4 modulates inflammation. 10 Previous studies have revealed that STEAP4 is overexpressed and related to invasion and metastasis in various cancers, including prostate, lung, and colon cancers; 3 , 31 , 32 STEAP4 is also associated with the immune response within the tumor microenvironment. 10 However, it is unclear whether STEAP4 affects carcinogenesis and immune reactions in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic liver disease, such as hepatitis B (HBV) or C virus (HCV), are primarily affected. 3 Currently, the decreasing prevalence of HBV and HCV and the rising prevalence of metabolic conditions, such as obesity, diabetes, and nonalcoholic fatty liver disease, appear to have altered the primary risk factors for HCC in many countries. 4 Notably, the fundamental essence of the onset and progression of HCC, which requires a multistep process of genetic alterations in hepatocytes through persistent inflammatory stimulation, remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“… 12 However, other molecules along with AFP have been widely studied with these aims, mainly Protein Induced by Vitamin K Absence (PIVKA – also known as DCP – Des-γ-carboxy prothrombin) and AFP L3 (subfraction of AFP), alone or included in algorithms and could be useful. 13 Underlying aetiology is not a key feature taken into account in the management of HCC to date.…”
Section: Introductionmentioning
confidence: 99%